K-Pop Fandom Activism on Social Media: Refuting Accusations of Slacktivism in Internet Activism - Putri Ananda Saka; Zidan Abdul Jabar Saka; Putri Rahmah Nurhakim; Mirna Yusuf; Yuniar Galuh Larasati; Rabiatul Adawiah (Fenomena)
The phenomenon of K-Pop fandom activism, which has been considered as a mere fanaticism movement, has experienced a developmental orientation towards the fulfillment of common interests. K-Pop fandom activism is able to become a movement in social media that has an impact and brings public attention in voicing social changes. This paper focuses on analyzing the trends, forms, and real implications of social movements initiated by K-Pop fandoms with a high number of masses and militants. Using qualitative research utilizing online sources, this study found that K-Pop fandom activism has enlivened issues that are not only related to their community but have referred to global issues such as social, cultural, environmental and political. This activism is able to become a catalyst on social media in the form of real action rather than slacktivism. Real action is carried out by giving donations, filling out petitions to make demonstration efforts. This activism phenomenon has implications for changes not only in the issues raised but also has implications for changes in the stigma of society towards K-Pop fandom which tends to be more positive as a driver of social change. However, this paper is limited to the use of text data as the main source which cannot provide empirical conclusions. Therefore, future research should integrate the views and experiences of those directly involved in K-Pop fandom activism so that it is possible to formulate more comprehensive conclusions.